Language Revitalization and Endangered Languages: Current Trends and Future Prospects - Yadav, Aditya Kumar (Journal of Advanced Research in English & Education, 2023)
Language revitalization has emerged as a crucial area of linguistic research and social policy, particularly in the context of preserving and revitalizing endangered languages. This review article provides an in-depth exploration of current trends, challenges, and promising strategies in the field of language revitalization. It synthesizes findings from diverse linguistic, anthropological, and educational perspectives, offering insights into the complex interplay between language, culture, and community dynamics. The review critically examines the criteria for identifying endangered languages, considering historical, social, and economic factors that contribute to their decline. It underscores the cultural and cognitive richness associated with linguistic diversity, setting the stage for a comprehensive discussion on revitalization efforts. A focal point of the review is an extensive exploration of various language revitalization strategies. Ranging from grassroots community initiatives to top-down government policies, these strategies encompass language immersion programs, intergenerational transmission initiatives, and the use of digital technologies. Challenges associated with language revitalization efforts, including funding constraints, institutional support, and issues of linguistic and cultural appropriation, are critically examined. Ethical considerations, such as the meaningful involvement of indigenous communities in decision-making processes, are woven into the fabric of the discussion. The pivotal role of education in language revitalization is dissected, with a focus on bilingual and multilingual education models. The section explores the integration of endangered languages into formal education systems and emphasizes the importance of fostering positive attitudes toward linguistic diversity among younger generations. In addition to traditional approaches, the review investigates the role of technology in language revitalization, including the use of digital platforms, mobile applications, and social media.